A novel two-stage hybrid processing technique towards industrial manufacturing of the Cu(In, Ga)(S, Se)2 solar cell with materially efficient fabrication. Issue 19 (29th April 2019) - Cho, Yunae; Youn, Na Kyoung; Song, Soomin; Hwang, Jiseon; Rana, Tanka Raj; Cho, Ara; Ahn, Seung Kyu; Kim, Kihwan; Yun, Jae Ho; Eo, Young-Joo; Gwak, Jihye
Abstract : The hybrid two-stage processing technique achieved the highly efficient CIGSSe solar cell with high material-utilization and a simple process for commercialization. Abstract : The chalcogenide Cu(In, Ga)(S, Se)2 (CIGSSe) solar cell is very promising because it exhibits one of the highest efficiencies among all thin-film solar cells. However, the expensive and complicated fabrication of these solar cells should be overcome for their successful commercialization. Herein, we investigated a novel fabrication technique that combined both vacuum and non-vacuum processes to minimize the production costs and increase the energy conversion efficiency. A carbon-free CuS nanoparticle precursor was used in the non-vacuum process to save Cu materials and the thermal budget. An (In, Ga)2 Se3 precursor was formed via vacuum co-evaporation, which provided control over the stoichiometry. The CIGSSe films were fabricated using two different approaches: (1) CuS was deposited on a Mo film, with subsequent co-evaporation of the (In, Ga)2 Se3 film (hybrid staking A – HSA) and (2) (In, Ga)2 Se3 was deposited on a Mo film, and then, CuS was formed on top of this with selenization (hybrid stacking B – HSB). The HSA solar cells had a higher quality structure and composition when compared with the HSB cells. The HSA CIGSSe solar cell exhibited the superior energy conversion efficiency of 13.6%. Our novel fabrication technique will contribute to the widespread commercialization of CIGSSe solar cells while minimizing material consumption.